Pengaruh Independensi, Keahlian Profesional, dan Pengalaman Kerja pada Kinerja Pengawas Koperasi Serba Usaha - Rurkiyasa Adi Putra, Komang; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi, 2020)
The purpose of this study was to determine the effect of independence, professional expertise, and work experience on the performance of Koperasi Serba Usaha. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that independence, professional expertise, work experience have a positive and significant effect on the performance of Multipurpose Cooperative supervisors in East Denpasar Sub-District. Adjusted R2 is 0.831. This shows that 83.1% of the variation in supervisor performance can be explained by the variables of independence, professional expertise, and work experience, while the remaining 16.9% is explained by other variables outside the model. Keywords: Independence, Professional Expertise; Work Experience; Employee; The Performance.